YIELD COMPONENTS OF MOTHBEAN (VIGNA ACONITIFOLIA (JACQ.) MARECHAL) AS INFLUENCED BY PHOSPHORUS AND BIO-FERTILIZERS - Kumar, SANTOSH; REAGER, M.L.; PAREEK, B.L (Annals of Agricultural Research, 2014)
A field experiment was conducted to the study the effect of four levels of phosphorus and four biofertilizers. The results showed that application of phosphorus significantly improved the yieldattributes viz., number of branches per plant, number of pods per plant, pod length, number of seeds per pod and 1000-grain weight, yield (seed, straw and biological yield), harvest index and benefit: cost ratio of mothbean upto 40 kg P2O5 ha-1 over control and lower doses. Dual inoculation with Rhizobium + phosphate solubilizing bacteria improved the yield attributes, yield and benefit: cost ratio over single inoculation either with Rhizobium or PSB and control. Single inoculation with Rhizobium remains statistically at par with inoculation with PSB, increased the all yield attributes, harvest index and benefit: cost ratio of mothbean over control.